2002
DOI: 10.1016/s0886-3350(02)01304-4
|View full text |Cite
|
Sign up to set email alerts
|

Photorefractive keratectomy in children

Abstract: Photorefractive keratectomy in children represents another method of providing long-term resolution of bilateral high myopia and myopic anisometropic amblyopia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
82
1
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(90 citation statements)
references
References 20 publications
2
82
1
5
Order By: Relevance
“…The paediatric eyes with some amount of amblyopia have improved (one line gain) and became independent of glasses. Few previous studies are available, conducting LASIK and PRK in children using Excimer Laser, [23][24][25][26] but this study included paediatric eyes for LASEK using solid state laser. It proves that it is easy to perform LASEK for the paediatric patients (12-14 years).…”
Section: Discussionmentioning
confidence: 99%
“…The paediatric eyes with some amount of amblyopia have improved (one line gain) and became independent of glasses. Few previous studies are available, conducting LASIK and PRK in children using Excimer Laser, [23][24][25][26] but this study included paediatric eyes for LASEK using solid state laser. It proves that it is easy to perform LASEK for the paediatric patients (12-14 years).…”
Section: Discussionmentioning
confidence: 99%
“…Loss of two lines of BCVA was 2-7.5 % for all groups. Only one study had shown severe haze at the rate of 2.5 % with one patient who had lost six lines of VA. 16 Endothelial cell loss increased from 1.4 % at 6 months to 3.6 % at 12 months. 13 Recently, a case of an acute hydrops with secondary bacterial keratitis as a sequela of paediatric refractive surgery was reported in a young adult with a history of trabeculectomy and PRK and RK around 5-6 years of age.…”
Section: -44mentioning
confidence: 93%
“…7,8 The high rate of regression is attributable to the enhanced healing properties in young eyes, eg, keratocyte-mediated regrowth and epithelial hyperplasia. Average regression can be about 1 D/y, 6,21,23,42 mainly in highly myopic eyes. For myopic children with treatment beyond 10 D, or hyperopic beyond 4.5 D, the regression may be 33% over a span of approximately 3 years.…”
Section: Gains In Visual Acuity and Visual Functionmentioning
confidence: 99%
“…6,21,23,42 Seldom is this due to increasing axial length. After age 2 to 3 years, axial length changes tend to be minor in highly ametropic phakic pediatric eyes.…”
Section: Gains In Visual Acuity and Visual Functionmentioning
confidence: 99%